Skip to content
Related Articles

Related Articles

Save Article
Improve Article
Save Article
Like Article

Class 10 RD Sharma Solutions – Chapter 14 Coordinate Geometry – Exercise 14.2 | Set 1

  • Last Updated : 30 Apr, 2021

Question 1. Find the distance between the following pair of points:

(i) (-6, 7) and (-1,-5)

(ii) (a + b, b + c) and (a – b, c – b)

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

(iii) (a sin a, -b cos a) and (-a cos a, b sin a)



(iv) (a, 0) and (0, b)

Solution:

(i) Given that P(-6, 7) and Q(-1, -5)

So, x1 = -6, y1 = 7 

x2 = -1, y2 = -5

Now we find the distance between PQ:

PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ PQ=\sqrt{[-1-(-6)]^2+(-5-7)^2}\\ PQ=\sqrt{(-1+6)^2+(-5-7)^2}\\ PQ=\sqrt{(5)^2+(-12)^2}\\ PQ=\sqrt{25+144}\\ PQ=\sqrt{169}\\ PQ=13\\

(ii) Given that P(a + b, b + c) and Q(a – b, c – b) 



So, x1 = a + b, y1 = b + c

x2 = a – b, y2 = c – b

Now we find the distance between PQ:

PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ PQ=\sqrt{[a-b-(a+b)]^2+(c-b-(b+c))^2}\\ PQ=\sqrt{(a-b-a-b)^2+(c-b-b-c)^2}\\ PQ=\sqrt{(-2b)^2+(-2b)^2}\\ PQ=\sqrt{4b^2+2b^2}\\ PQ=\sqrt{8b^2}\\ PQ=\sqrt{4*2b^2}\\ PQ=2\sqrt{2b}

(iii) Given that P(a sin a,-b cos a) and Q(-a cos a, b sin a)

So, x1 = a sin a, y1 = -b cos a

x2 = a cos a, y2 = b sin a

Now we find the distance between PQ:

PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ PQ=\sqrt{(-a\cos a-a\sin a)^2+[-b\sin a-(-b\cos a)]^2}\\ PQ=\sqrt{(-a\cos a)^2+(-a\sin a)^2+2(a-\cos a)(-a\sin a)+(b\sin a)^2+(-b\cos a)^2-2(b\sin a)(-b\cos a)}\\ PQ=\sqrt{a^2cos^2a+a^2\sin^2a+2a^2\cos a\sin a+b^2\sin^2a+b^2\cos^2a+2b^2\sin a\cos a}\\ PQ=\sqrt{a^2(\cos^2a+\sin^2a)+2a^2\cos a\sin a+b^2(\sin^2a+\cos^2a)+2b^2\sin a\cos a}\\ PQ=\sqrt{a^2*1+2a^2\cos a\sin a+b^2*12b^2\sin a\cos a}\\ PQ=\sqrt{a^2+b^2+2a^2\cos a\sin a+2b^2\sin a\cos a}\\ PQ=\sqrt{(a^2+b^2)+2\cos a\sin a(a^2+b^2)}\\ PQ=\sqrt{(a^2+b^2)+(1+2\cos a\sin a)}\\

(iv) Given that P(a, 0) and Q(0, b)



So, x1 = a, y1 = 0

x2 = 0, y2 = b

Now we find the distance between PQ:

PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ PQ=\sqrt{(0-a)^2+(b-0)^2}\\ PQ=\sqrt{(-a)^2+(b)^2}\\ PQ=\sqrt{a^2+b^2}\\

Question 2. Find the value of a when the distance between the points (3, a) and (4, 1) is √10.

Solution:

Given that point P(3, a) and Q(4, 1) and the distance between them is √10

So, we have to find the value of a

So, 

 PQ=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ \sqrt{10}=\sqrt{(4-3)^2+(1-a)^2}\\ \sqrt{10}=\sqrt{(1)^2(1-a)^2}\\ \sqrt{10}=\sqrt{1+1+a^2-2a}\\ \sqrt{10}=\sqrt{2+a^2-2a}

Squaring on both sides we get 



(√10)2 = (√{2 + a2 – 2a})2 

10 = 2 + a2 – 2a

a2 – 2a + 2 – 10 = 0

a2 – 2a – 8 = 0

On Splitting the middle term we get 

a2 – 4a + 2a – 8 = 0

a(a – 4) + 2(a – 4) = 0

(a – 4)(a + 2) = 0 

a = 4, a = -2

Question 3. If the points (2, 1) and (1, 2) are equidistant from the point(x, y) show that x + 3y = 0.

Solution:

Given that P(2, 1) and Q(1, -2) and R(x, y)

Also, PR = QR

PR=\sqrt{(x-2)^2+(y-1)^2}\\ PR=\sqrt{x^2(2)^2-2xx*2+y^2+(1)^2-2*y*1}\\ PR=\sqrt{x^2+4-4x+y^2+1-2y}\\ PR=\sqrt{x^2+5-4x+y^2-2y}\\ QR=\sqrt{(x-1)^2+(y+2)^2}\\ PR=\sqrt{x^2+1-2x+y^2+4+4y}\\ PR=\sqrt{x^2+5-2x+y^2+4y}\\ PR=QR\\ \sqrt{x^2+5-4x+y^2-2y}=\sqrt{x^2+5-2x+y^2+4y}

x2 + 5 – 4x + y2 – 2y = x2 + 5 – 2x + y2 + 4y

x2 + 5 – 4x + y2 – 2y = x2 + 5 – 2x + y2 + 4y 

-4x + 2x – 2y – 4y = 0 

-2x – 6y = 0

 -2(x + 3y) = 0

x + 3y = 0/-2 

x + 3y = 0



Hence Proved

Question 4. Find the values of x, y if the distance of the point(x, y) from(-3, 0) as well as from (3, 0) are 4.

Solution:

Given that P(x, y), Q(-3, 0) and R(3, 0). 

Also, PQ = PR = 4

So, 

PQ=\sqrt{(x+3)^2+(y-0)^2}\\ 4=\sqrt{x^2+9+6x+y^2}

On squaring on both sides, we get 

(4)2 = (√x2 + 9 + 6x + y2)2 

16 = x2 + 9 + 6x + y2 

x2 + y2 = 16 – 9 – 6x

x2 + y2 = 7 – 6x ……..(1)

PR=(\sqrt{(x-3)^2+(y-0)^2})\\ 4=\sqrt{x^2+9-6x+y^2}

On squaring on both sides, we get

(4)2 = (√x2 + 9 – 6x + y2)2 

16 = x2 + 9 – 6x + y2

x2 + y2 = 16 – 9 + 6x

x2 + y2 = 7 + 6x  ……..(2)

From equation (1) and (2)

7 – 6x = 7 + 6x

7 – 7 = 6x + 6x

0 = 12x

x = 12

On substituting the value of x = 0 in eq(2)

x2 + y2 = 7 + 6x

0 + y2 = 7 + 6 * 0

y2 = 7

y = ±√7

Question 5. The length of a line segment is of 10 units and the coordinates of one end-point are (2, -3). If the abscissa of the other end is 10, find the coordinate of the other end.

Solution:

Let the ordinate of other end by y, then The distance between (2, -3) and (10, y) is

=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(10-2)^2+(y+3)^2}   = 10 



Squaring on both sides we get

(8)2 + (y + 3)2 = 100

64 + y2 + 6y + 9 = 100

y2 + 6y + 73 – 100 = 0

y2 + 6y – 27 = 0 

y2 + 9y – 3y – 27 = 0

y(y + 9) – 3(y + 9) = 0

(y + 9)(y – 3) = 0

When y + 9 = 0, then y = -9

or when y – 3 = 0, then y = 3 

So, the coordinates will be -9 or 3

Question 6. Show that the points (-4, -1), (-2, -4), (4, 0), and (2, 3) are the vertices points of a rectangle. 

Solution:

Let us considered ABCD is a rectangle whose vertices are

A(-4, -1), B(-2, -4), C(4, 0) and D(2, 3)

Now 

AB = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}

\sqrt{(-2+4)^2+(-4+1)^2}\\ =\sqrt{(2)^2+(-3)^2}=\sqrt{4+9}=\sqrt{13}

Similarly, CD =√13 

AD = √52

and BC = √52

AC = √65 and BD = √65

Here, AB = CD and AD = BC

and diagonals AC = BD

So, ABCD is a rectangle

Question 7. Show that the points A (1, -2), B (3, 6), C (5, 10), and D (3, 2) are the vertices of a parallelogram.

Solution:

Given points are A (1, -2), B (3, 6), C (5, 10) and D (3, 2)

Now AB = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(3-1)^2+(6+2)^2}=\sqrt{(2)^2+(8)^2}\\ =\sqrt{4+64}=\sqrt{68}

Similarly BC = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(2)^2+(4)^2}=\sqrt{20}\\ CD=\sqrt{(3-5)^2+(2-10)^2}\\ =\sqrt{(-2)^2+(-8)^2}=\sqrt{4+64}=\sqrt{68} \\DA=\sqrt{(3-1)^2+(2+2)^2}\\ \sqrt{(2)^2+(4)^2}=\sqrt{20}

So, from the above we conclude that AB = CD and AD = BC

Hence, ABCD is a parallelogram.



Question 8. Prove that the points A (1, 7), B (4, 2), C (-1, -1), and D (-4, 4) are the vertices of a square. 

Solution:

Given points are A (1, 7), B (4, 2), C (-1,-1), D (-4, 4)

If these are the vertices of a square, then its diagonals and sides are equal

AC = \sqrt{(1+1)^2+(7+1)^2}=\sqrt{2^2+8^2}\\ =\sqrt{4+64}=\sqrt{68}\\ BD=\sqrt{(4+4)^2+(2-4)^2}=\sqrt{(8)^2+(-2)^2}\\ =\sqrt{64+4}=68

So, AC = BD

Now AB=\sqrt{(1-4)^2+(7-2)^2}\\ =\sqrt{(-3)^2+(5)^2}=\sqrt{9+25}=\sqrt{34}\\ BC=\sqrt{(4+1)^2+(2+1)^2}=\sqrt{(5)^2+(3)^2}\\ =\sqrt{25+9}=\sqrt{34}\\ CD=\sqrt{(-1+4)^2+(-1+4)^2}\\ =\sqrt{(3)^2+(-5)^2}=\sqrt{9+25}=\sqrt{34}\\DA=\sqrt{(1+4)^2+(2-4)^2}\\ =\sqrt{(5)^2+(3)^2}=\sqrt{25+9}=\sqrt{34}

So, AB = BC = CD = DA and diagonal AC = BD

Hence, the given figure ABCD is a square.

Question 9.Prove that the points (3, 0), (6, 4), and (-1, 3) are the vertices of a right-angled isosceles triangle.

Solution:

Given points are A(3, 0), B(6, 4), and C(-1, 3)



Now we find the length of AB = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(6-3)^2+(4-0)^2}=\sqrt{(3)^(4)^2}\\ \sqrt{25}=5

Similarly, BC=\sqrt{(-1-6)^2(3-4)^2}=\sqrt{(7)^2(-1)^2}\\ \sqrt{49+1}=\sqrt{50}\\ CA=\sqrt{(3+1)^2(0-3)^2}=\sqrt{(4)^2(3)^2}\\ =\sqrt{16+9}=\sqrt{25}=5

From the above we conclude that AB = CA and BC is the longest side

Now we verify the Pythagoras theorem,

So, BC2 = AB2 + CA

BC2 = (5)2 + (5)2 

BC2 = 25 + 25 

50 = 50

So, AB2 + CA2 = BC2

Hence, the given triangle ABC is an isosceles right triangle.

Question 10. Prove that (2, -2), (-2, 1), and (5, 2) are the vertices of a right-angled triangle. Find the area of the triangle and the length of the hypotenuse.

Solution:

Given points are A(2, -2), B(-2, 1) and C(5, 2)

Now we find the length of AB=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(-2-2)^2+(1+2)^2}=(-4)^2+(3)^2\\ \sqrt{25}=5\\ BC=\sqrt{(5+2)^2+(2-1)^2}\\ =\sqrt{(7)^2+(1)^2}=\sqrt{49+1}=\sqrt{50}\\ CA=\sqrt{(3+1)^2+(0-3)^2}=\sqrt{(4)^2+(-3)^2}\\ \sqrt{16+9}=\sqrt{25}=5

We see that AB = CA and BC is the longest side.

Now we verify the Pythagoras theorem,

So, BC2 = AB2 + CA

BC2 = (5)2 + (5)2 

BC2 = 25 + 25 

50 = 50

So, AB2 + CA2 = BC2



So, the given triangle ABC is a right-angled triangle

Now we find the area of triangle ABC = 1/2 × Base × height 

= 1/2 × 5 × 5

= 25/2 sq.units

And the length of the hypotenuse BC is √50.

Question 11. Prove that the points (2a, 4a), (2a, 6a), and (2a + √3 a, 5a) are the vertices of an equilateral triangle.

Solution:

Given points are A(2a, 4a), B(2a, 6a) and C(2a + √3 a, 5a)

Now we find the length of AB=\sqrt{(x_2-x_1)^2+)(y_2-y_1)^2}\\ =\sqrt{(2a-2a)^2+)(6a-4a)^2}\\ \sqrt{0+4a^2}=\sqrt{4a^2}=2a\\ BC=\sqrt{(2a+\sqrt{3a}-2a)^2+(5a-6a)^2}\\ =\sqrt{3a^2+a^2}\\ =\sqrt{4a^2}=2a \\ CA=\sqrt{(2a-2a-\sqrt{3a})^2(4a-5a)^2}\\ \sqrt{3a^2+a^2}\\ =\sqrt{4a^2}=2a

So, we conclude that the length of side AB = BC = CA = 2a

Hence, ∆ABC is equilateral triangle. 

 Question 12. Prove that the points (2, 3), (-4, -6), and (1, 32) do not form a triangle.

Given points are A(2, 3), B(-4, -6), and C(1, 32)

Now we find the length of AB = \sqrt{(x_2-x_1)^2+)(y_2-y_1)^2}\\ =\sqrt{(-4-2)^2+(-6-3)^2}\\ \sqrt{36+81}=\sqrt{117}\\

Similarly, for BC = √89 and CA = √2 

As we know that the sum of two sides of triangle are always greater than the third side

So, BC + CA= √89 + √2 not greater than AB 

Hence, the given points do not form a triangle.

Question 13. The points A (2, 9), B (a, 5), and C (5, 5) are the vertices of a triangle ABC right-angled at B. Find the values of a and hence the area of ∆ABC. 

Solution:

Given that, the points A (2, 9), B (a, 5) and C (5, 5) are the vertices of ∆ABC right-angled at B.

By Pythagoras theorem, 

AC2 = AB2 + BC2 ………(i)

Now, by distance formula,

We find the length of AB = \sqrt{(a-2)^2+(5-9)^2}

= \sqrt{a^2+4-4a+16}=\sqrt{a^2-4a+20}\\ BC=\sqrt{(5-a)^2+(5-5)^2}\\ =\sqrt{(5-a)^2+0}=5-a\\ AC=\sqrt{(2-5)^2+(9-5)^2}\\ =\sqrt{(-3)^2+(4)^2}=\sqrt{9+16}=\sqrt{25}=5     ]

Now put the values of AB, BC and AC in equation(i), we get

(5)^2=\sqrt{(a^2-4a+20)^2+(5-a)^2}

25 = a2 – 4a + 20 + 25 + a2 – 10a

2a2 – 14a + 20 = 0

a2 – 7a + 10 = 0

a2 – 2a – 5a + 10 = 0

a(a – 2) – 5(a – 2) = 0



(a – 5)(a – 5) = 0

a = 2, 5

Here, a ≠ 5, since at a = 5, the length of BC = 0. It is not possible because  

the sides AB,BC and CA from a right angled triangle.

So, a = 2

Now, the coordinates are A (2, 9), B (2, 5) and C (5, 5)

Now we find the area of ∆ABC = \frac{1}{2}[x_1(y_2-y_3)+x_2(y_3-y_1)+x_3(y_1-y_2)]

= 1/2[2(5 – 5) + 2(5 – 9) + 5(9 – 5)]

= 1/2(0 – 8 + 20) 

= 1/2 × 12

= 6

Hence, the required area of ∆ABC is 6sq. units.

Question 14. Show that the quadrilateral whose vertices are (2, -1), (3, 4), (-2, 3), and (-3, -2) is a rhombus.

Solution:

Given points are A(2, -1), B(3, 4), C(-2, 3), and D(-3, -2)

Now we find the length of sides AB, CD, DA, BD and diagonals AC, BD

AB=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(3-2)^2+(4+1)^2}=\sqrt{(1)^2+(5)^2}=\sqrt{1+25}=\sqrt{26}\\ BC=\sqrt{(-2-3)^2+(3-4)^2}\\ \sqrt{(-5)^2+(-1)^2}=\sqrt{25+1}=\sqrt{26}\\ CD=\sqrt{(-3+2)^2+(-2-3)^2}=\sqrt{(-1)^2+(-5)^2}=\sqrt{1+25}=\sqrt{26}\\DA=\sqrt{(2+3)^2+(-1+2)^2}\\ =\sqrt{(5)^2+(1)^2}=\sqrt{25+1}=\sqrt{26}\\AC=\sqrt{(-2-2)^2+(3+1)^2}\\ =\sqrt{(-4)^2+(4)^2}=\sqrt{16+16}=\sqrt{32} \\BD=\sqrt{(-3-3)^2+(-2-4)^2}\\ =\sqrt{(-6)^2+(-6)^2}=\sqrt{36+36}=\sqrt{72}

Now we conclude that AB = BC = CD = DA = √26 and diagonal AC ≠ BD

Hence, ABCD is a rhombus

Question 15. Two vertices of an isosceles triangle are (2, 0) and (2, 5). Find the third vertex if the length of the equal sides is 3.

Solution:

Let us considered ABC is an isosceles triangle whose two vertices are A (2, 0) and B (2, 5)

So, the co-ordinates of third vertex C be (x, y)

And also given that AC = BC = 3

Now AC=\sqrt{(x-2)^2+(y-0)^2}\\ =\sqrt{(x-2)^2+y^2}\\ \sqrt{(x-2)^2+y^2}=3

On squaring both sides, we get

(x – 2)2 + y2 = 9                        

x2 – 4x + 4 + y2 = 9

x2 + y2 – 4x =  5             …….(i)

Similarly, BC=\sqrt{(x-5)^2+(y-5)^2}\\ \sqrt{(x-2)^2+(y-5)^2}=3

On squaring both sides, we get



(x – 2)2 + (y – 5)2 = 9               

x2 – 4x + 4 + y2 – 10y + 25 = 9

x2 + y2 – 4x – 10y = -20             …….(ii)

Now on subtracting eq(ii) from (i), we get

10y = 25

y = 25/10 = 5/2

On substituting the value of y in eq(i)

x2 – 4x + (5/2)2 = 5

x2 – 4x + 25/4 – 5 = 0

4x2 – 16x + 25 – 20 = 0

4x2 – 16x + 5 + 5 = 0

Here a = 4, b = -16, c = 5

x=\frac{-b±\sqrt{b^2-4ac}}{2a}\\ \frac{-(-16)±\sqrt{(-16)^2-4\times 4\times 5}}{2\times 4}\\ =\frac{16±\sqrt{256-80}}{8}=\frac{16±\sqrt{179}}{8}\\ =\frac{16±\sqrt{16\times 11}}{8}\\ =\frac{16±4\sqrt{11}}{8}=\frac{4±\sqrt{11}}{2}=2±\frac{\sqrt{11}}{2}

So, the co-ordinate of C will be (2 + √11/2, 5/2) or (2 – √11/2, 5/2)

Question 16. Which point on x-axis is equidistant from (5, 9) and (-4, 6)?

Solution:

Let co-ordinates of two points are A (5, 9), B (-4, 6)

The required point is on x-axis

Its ordinates or y-co-ordinates will be 0

Let the co-ordinates of the point C be (x, 0)

AC = CB

Now AC=\sqrt{(x-5)^2+(0-9)^2}=\sqrt{(x-5)^2+81}\\ and\space CB=\sqrt{(x+4)^2+(0-6)^2}=\sqrt{(x+4)^2+36}

\sqrt{(x-5)^2+81}=\sqrt{(x+4)^2+36}

Squaring both sides, we get

(x – 5)2 + 81 = (x + 4)2 + 36

x2 – 10x + 25 + 81 = x2 + 8x + 16 + 36 – 10x – 8x

-18 = 52 – 106

-18x = -54

x = -54/18

x = 3

Hence, the required point is (3, 0)

Question 17. Prove that the point (-2, 5), (0, 1) and (2, -3) are collinear.

Solution:

Given points are A(-2, 5), B(0, 1) and C(2, -3)

Now we find the length of AB, BC, and CA

AB=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(0+2)^2+(1-5)^2}\\ =\sqrt{(2)^2+(-4)^2}=\sqrt{4+16}\\ \sqrt{20}=\sqrt{4*5}=2\sqrt{5}\\BC=\sqrt{(2-0)^2+(-3-1)^2}\\ =\sqrt{(2)^2+(-4)^2}\\ =\sqrt{4+16}=\sqrt{20}=\sqrt{4*5}=2\sqrt{5}\\ CA=\sqrt{(-2-2)^2+(5+3)^2}\\ =\sqrt{(-4)^2+(8)^2}=\sqrt{16+64}\\ \sqrt{80}=\sqrt{16*5}=4\sqrt{5}

Now AB + BC = 2√5 + 2√5

And CA = 4√5

AB + BC = CA

Hence, A, B and C are collinear

Question 18. The coordinates of the point P are (-3, 2). Find the coordinates of the point Q which lies on the line joining P and origin such that OP = OQ.

Solution:

Given that the co-ordinates of P are (-3, 2) and origin O are (0, 0)



Let us assume that the co-ordinates of Q be (x, y)

Here, O is the mid-point of line PQ

so by using mid point formula we get,

(x – 3)/2 = 0 and (y + 3)/2 = 0

x = 3, y = -2

Hence, the coordinates of the point Q are (3, -2)

Question 19. Which point on y-axis is equidistant from (2, 3) and (-4, 1)?

Solution:

The required point lies on y-axis

Its abscissa will be zero

So, let us assume that the point be C (0, y) and A (2, 3), B (-4, 1)

Now, we find the length of AC and BC

AC=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\ =\sqrt{(0-2)^2+(y-3)^2}\\ =\sqrt{(-2)^2+(y-3)^2}=\sqrt{4+(y-3)^2}\\BC=\sqrt{(0-4)^2+(y-1)^2}\\ =\sqrt{16+(y-1)^2}\\

Here, we conclude that AC = BC

So, \sqrt{4+(y-3)^2}=\sqrt{16+(y-1)^2}

On squaring both sides, we get

4 + (y – 3)2 = 16 + (y – 1)2

4 + y2 + 9 – 6y = 16 + y2 + 1 – 2y

-6y + 2y = 17 – 13

-4y = 4 = y = 4/-4 = 1

Hence, the coordinates of the required point is (0,-1)




My Personal Notes arrow_drop_up
Recommended Articles
Page :